LEARNING PROCESS OF INTRODUCTION TO LAMPUNG SCRIPT THROUGH ICT (INFORMATION AND COMMUNICATION TECHNOLOGIES) FOR KINDERGARTEN STUDENTS OF TK RASYIDUL JANNAH BANDAR LAMPUNG ACADEMIC YEAR 2014-2015 - Dharlinda Suri (Proceeding International Conference on Information Technology and Business, 2015)
Problems proposed in this study are: (1) How isthe learning process of introduction to Lampung scriptfor kindergarten students through ICT? (2) What aresupporting and inhibiting factors in the learning processof introduction to Lampung script for kindergartenstudents through ICT?The objectives of the research are: (1) to describethe learning process of introduction to Lampung scriptfor kindergarten students through ICT and (2) to describesupporting and inhibiting factors in the learning processof introduction to Lampung script for kindergartenstudents through ICT.This research was conducted at Rasyidul JannahKindergarten, Bandar Lampung. As the focuses of thisresearch are the kindergarten teachers and 24 studentsgroup B aged 5-6 years. This research took place in thesecond semester of the academic year 2014-2015. Thisstudy uses qualitative descriptive approach as theresearcher describes all the process related to thelearning process of introduction to Lampung script doneby the teachers through ICT. This study used aqualitative descriptive approach, where researcher triedto describe all the events in relation to the introduction ofLampung script done by teachers through ICT. Thefinding of this research suggested that ICT is effective tohelp these kindergarten students in the learning processof introduction to Lampung script. The supportingfactors in introduction to Lampung script learning are theteachers, the students and surrounding society whoshowed enthusiasm in the learning process. Meanwhile,the inhibiting factors are students’ difficulties inpronouncing the alphabets and some similar scriptwriting shapes. In accordance with this research finding,it is recommended for the management of earlychildhood education to provide VCD of Lampung scriptlearning animation and for the kindergarten teachers tocarry out teaching Lampung script using the VCD as partof teacher’s professional skills.Keywords: Learning, Early Childhood, Animation,Lampung script